Health conditions and Nurses' work characteristics at a university hospital - Cláudia Jeane Lopes Pimenta; Mateus Carneiro Vicente; Gerlania Rodrigues Salviano Ferreira; Maria Cristina Lins de Oliveira Frazão; Tatiana Ferreira da Costa; Kátia Neyla de Freitas Macedo Costa (Universidade Federal do Ceará, 2020)
Objective: to analyze the sociodemographic profile, health conditions, and nurses' work characteristics. Methods: a cross-sectional study conducted with 152 nurses from a university hospital. We used a structured instrument analyzed using descriptive statistics. Results: nurses considered their health good (50.7%), performed physical activity (53.3%), did not smoke (92.8%), did not consume alcohol (56.6%), had some health problems (63.2%) and used medication daily (54.6%). There was a higher number of professionals working in the outpatient clinic (17.8%) and emergency medicine (15.8%), who worked in the studied hospital for up to five years (61.2%), were employees subject to the Consolidation of Labor Laws (74.3%), without another employment relationship (54.6%), day shift (56.6%), had a six-hour schedule (36.2%), reported absence from work for up to five days (38.2%), due to health problems (41.4%). Conclusion: we noticed the presence of illness processes among professionals, which can interfere in the quality and safety of care.